Media Studies 2.0: upgrading and open-sourcing the discipline - Merrin, William (Interactions: Studies in Communication & Culture, 2009)
This paper argues that media studies needs to be upgraded to reflect contemporary changes in digital media. It argues that media studies was a product and reflection of the broadcast-era of media, being formed in and analysing a specific historical period of media production, distribution and consumption. The rise of digital media, the transformation of old media into a digital form and ongoing developments in digital technology take us into a post-broadcast era, defined by new alignments of productive and distributive power and media consumption and use. This requires an upgraded Media Studies 2.0, marked by the revision and updating of existing disciplinary knowledge; the foregrounding of contemporary changes and the development of new categories and concepts to understand these, and the open-sourcing of the discipline itself laying open its foundation, assumptions and biases to enable its public to continually rewrite and improve its knowledge, to ensure its continued relevance in a rapidly changing era.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9pc2NjLjEuMS4xN18x